Human Resource Management in Small and Medium-Sized Vineyards in Chile [Administración de Recursos Humanos en Pequeñas y Medianas Viñas en Chile] - Perez-Arrau, J; Muñoz-Medina, L (Pontificia Universidad Catolica de Chile, Facultad de Agronomia e Ingenieria Forestal, 2014)
The focus of this paper is the identification of human resource management practices in small and medium-sized vineyards in Chile, identifying agents and relevant groups that allow a better understanding of how these companies manage their human resources. The research is based on 22 interviews held with personnel managers and key informants from a total of 16 wine-producing vineyards between 2009 and 2012. The research involved collecting studies and analyzing the specialized literature on human resource management in small and medium-sized enterprises (SMEs). The research highlights the features, relevant problems and challenges of human resources management with the aim of improving production, innovation and long-term sustainability. Although the wine industry is an emblematic economic area of Chile, how it manages its human resources is unknown, so this research focuses on this little-known area that is so important to productivity. © 2014 Pontificia Universidad Catolica de Chile, Facultad de Agronomia e Ingenieria Forestal. All rights reserved.